(3GdSjQ hGdWjQs - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3SjQhG SHb GdeaQOhf bjd ef GdeaQOhf jG QShd Gddg ? bGd GdeSJgJQhf HPcQ Gddg , hUfY GdPcQ Yfge ChRGQge , ahQOhG GdbjGeI NaGakG s
(3BNQgG (B:s
(3hef CTGQ Zdi TF ef GdWjQ eJNQeI Ydjg bGYOI GdELJgGO HJMbjb eHGfi GdESdGe age eOYi Edi Cf jche eaJjkG JhGHkG Je GdcdGe ai GdWjQ hGdSjQ hGdMeO deSJMb GdMeO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B198 - (3U(B213s
(3HgG fXGe GdJYbjHIs
(3Ydi GdeLehYI JedcGJ CbOegG SfI (B987(3g`s
(3HBNQgG CLhHI deSGFd SFd YfgG GdSgQhQOi hfbhd ef cdGegs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs